The Protection of Foreigners in International Law - Ferry Eka Rachman (Journal La Sociale, 2021)
This research aims to find out legal protection against foreigners and citizens who lives outside their nationality country. In discussing the issue of international legal protection against foreigners, a doctrinal approach and international court practice is used. From the opinion of international legal experts, it will be found legal principles and theories regarding the position of individuals as subjects of international law. The principles of citizenship are the main basis for the application of the principle of jurisdiction and country responsibility towards its citizens and foreigners.The results are, In principle, every country will be responsible for providing legal protection to every citizen of the country wherever he/she is and foreigners will receive legal protection, under certain limitations, both from the country where he/she is temporarily located and from the country of origin. Thus, a person's citizenship status is closely related to the protection of international law that will be given to him/her, against him/her, his/her property and family. The application of the principle of state responsibility against citizens abroad or foreigners is based more on the principle of state sovereignty. A sovereign state will apply its national laws to its citizens within its territorial boundaries. Apart from that what applies is legal provisions of other countries or provisions of international law.